Abordagem fotomorfogenética para explorar o estresse abiótico em tomateiro (Solanum lycopersicum L.) - Gavassi, Marina Alves [UNESP] (2015)
Phytochrome are the most characterized plant photoreceptor. It controls several responses from germination to flowering. These molecules are protein covalently bound to a chromophore, where the protein portion (apoprotein) is encoded by a small gene family. In tomato, for example, one of the most important vegetable crops in the world, five genes were found to apoproteins: PHYA, PHYB1, PHYB2, PHYE and PHYF. Thus, photomorphogenic mutants in tomato, such as mutants defective in the biosynthesis of the phytochrome apoproteins (or far red insensitive fri), B1 (temporary or tri insensitive red) and B2 (phyB2) has become indispensable tools to better understand the functions of phytochrome in several responses, including those of great agroeconomic importance as biotic and abiotic stresses. In fact, recent evidence shows that the family of the phytochrome A and B are an important mediator of abiotic stress. For a better understanding of the biochemical and physiological relations of phytochrome with responses to stress, growth analyzes were performed, as well as osmolytes accumulation compatible, pigment content and lipid peroxidation. It can be concluded that tomato phytochrome B1 and B2 act as an important signaling during development of seedlings in abiotic stress conditions induced by drought, high salinity, excess cadmium, high temperature and UV-B radiation